Recording practices of body mass index, overweight and obesity by Dutch general practitioners: an observational study - Willemijn J. van den Hout; Petra G. van Peet; Mattijs E. Numans; Dennis O. Mook-Kanamori (BMC Primary Care)
Abstract Background Routine body mass index (BMI) recording in electronic health records (EHR) could support general practitioners (GPs) in managing patients with obesity. This study aimed to evaluate recording practices of BMI, overweight, and obesity in adults including subgroup analysis of age, sex, and comorbidities in primary care in the Netherlands. Methods An observational study of individuals aged ≥ 18 years and registered between 2007 and 2023, using routine healthcare data from the Extramural LUMC Academic Network (ELAN) in the Netherlands. Outcomes were (i) incidence rates of a recorded BMIs per 1000 person-years for sex and ten-year age categories (ii) proportions of recorded BMIs for different comorbidities and (iii) proportions of diagnosis of overweight (BMI between 25 and 30 kg/m2) and/or obesity (BMI ≥ 30 kg/m2) for a corresponding recorded BMI. Results Approximately 30% of 676,708 individuals had a recorded BMI. Highest incidence rate (186 per 1000 person-years) was at age 71 to 80 years. At least one BMI was recorded in 68.5% individuals with chronic obstructive pulmonary disease, 70.6% with hypertension, 86.3% with type II diabetes, 42.4% with eating disorders, 36% with depression and 64.2% with osteoarthritis. Diagnoses of overweight and/or obesity were found in 11.5% individuals with a BMI between 25 and 30 kg/m2 and in 36.4% with a BMI of ≥ 30 kg/m2. Conclusion In the Netherlands, GPs recorded BMIs in nearly one third of all adults, mainly in adults with chronic diseases. Routinely recording BMI is not currently standard practice. With the increasing prevalence of obesity and its related comorbidities, it may be beneficial to start routinely recording BMI in primary care.